Mejoramiento genético. Mejoramiento de caracteres. Nutrición y calidad - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Several groups of EP (preliminary trials) var. were evaluated in the nutrition and quality lab. for grain quality, percentage water absorption from dry wt., presence of hard and broken grains, av. cooking time, broth quality, and protein content. Significant differences were found in the av. values of all the characteristics measured in the EP/82, 84, and 85 with the exception of protein content of the EP/82 and 84 and for solids in the broth. In addition, a comparative study was conducted on the influence of the location, harvest period, and var. on cooking time, hardness, and protein content to determine whether genetic variability or environmental variability or their interaction exists. The results of the various trials are presented in table form. (CIAT)